2008
DOI: 10.1007/s00204-008-0341-7
|View full text |Cite
|
Sign up to set email alerts
|

ER-stress caused by accumulated intracistanal granules activates autophagy through a different signal pathway from unfolded protein response in exocrine pancreas cells of rats exposed to fluoride

Abstract: In rat exocrine pancreas cells, fluoride treatment causes autophagy resulting from intracisternal granule accumulation. Excessive autophagy might promote a type of programmed cell death different from apoptosis. To clarify how fluoride-induced autophagy and subsequent cell death occurs, we investigated morphological and biochemical changes in exocrine pancreas cells of rats subcutaneously injected with NaF saline solution at 20 mg/kg dose twice daily for 4 days. Intracisternal granule, excessive autophagy and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
22
0

Year Published

2009
2009
2023
2023

Publication Types

Select...
8
2

Relationship

1
9

Authors

Journals

citations
Cited by 44 publications
(22 citation statements)
references
References 40 publications
0
22
0
Order By: Relevance
“…As for the relationship of autophagy and cell viability, many studies have reported that autophagy is primarily a pro-survival rather than a pro-death mechanism (27, 28). Although some studies argue that excessive autophagy might promote cell death and the intense degranulation may be the turning point that commits damaged cells to death process rather than cell protective process (29), the molecular mechanisms of autophagy induced cell death remain poorly understood.…”
Section: Discussionmentioning
confidence: 99%
“…As for the relationship of autophagy and cell viability, many studies have reported that autophagy is primarily a pro-survival rather than a pro-death mechanism (27, 28). Although some studies argue that excessive autophagy might promote cell death and the intense degranulation may be the turning point that commits damaged cells to death process rather than cell protective process (29), the molecular mechanisms of autophagy induced cell death remain poorly understood.…”
Section: Discussionmentioning
confidence: 99%
“…These cells also respond to ER stress by increased expression of GADD45α, a p53-regulated and DNA damage-inducible protein, which is not a part of UPR but has recently been demonstrated to play a role in a cell cycle checkpoint arresting cells at G2/M phase in response to DNA damage [153]. In exocrine pancreas cells, the fluoride-induced ER stress was shown to increase eIF2α phosphorylation and CHOP expression, but did not affect GRP78, while spliced XBP-1 expression was decreased, indicating that ER stress under influence of fluoride can also activate another type of cell death, autophagy, without UPR [154].…”
Section: Endoplasmic Reticulum Stressmentioning
confidence: 99%
“…For example, genes mediating endoplasmic reticulum (ER) stress, such as the ER chaperone GRP78, are upregulated with repetitive ischemia, but not in traditional preconditioning. 18 ER stress activates autophagy in yeast 24 and different cell types, 25 and the ER chaperone GRP78 is required for stress-induced autophagy. 26 Beclin 1, a mediator of autophagy, primarily localizes to the ER in mammalian cells.…”
Section: Autophagy In Ischemic Preconditioning and Hibernating Myocarmentioning
confidence: 99%